Brain Metabolism Alterations Induced by Pregnancy Swimming Decreases Neurological Impairments Following Neonatal Hypoxia-Ischemia in Very Immature Rats - Sanches, Eduardo F.; Van de Looij, Yohan; Toulotte, Audrey; da Silva, Analina R.; Romero, Jacqueline; Sizonenko, Stephane V. (Frontiers in Neurology, 2018)
Introduction: Prematurity, through brain injury and altered development is a major cause of neurological impairments and can result in motor, cognitive and behavioral deficits later in life. Presently, there are no well-established effective therapies for preterm brain injury and the search for new strategies is needed. Intra-uterine environment plays a decisive role in brain maturation and interventions using the gestational window have been shown to influence long-term health in the offspring. In this study, we investigated whether pregnancy swimming can prevent the neurochemical metabolic alterations and damage that result from postnatal hypoxic-ischemic brain injury (HI) in very immature rats. Methods: Female pregnant Wistar rats were divided into swimming (SW) or sedentary (SE) groups. Following a period of adaptation before mating, swimming was performed during the entire gestation. At postnatal day (PND3), rat pups from SW and SE dams had right common carotid artery occluded, followed by systemic hypoxia. At PND4 (24h after HI), the early neurochemical profile was measured by 1H-magnetic resonance spectroscopy. Astrogliosis, apoptosis and neurotrophins protein expression were assessed in the cortex and hippocampus. From PND45, behavioral testing was performed. Diffusion tensor imaging and neurite orientation dispersion and density imaging were used to evaluate brain microstructure and the levels of proteins were quantified. Results: Pregnancy swimming was able to prevent early metabolic changes induced by HI preserving the energetic balance, decreasing apoptotic cell death and astrogliosis as well as maintaining the levels of neurotrophins. At adult age, swimming preserved brain microstructure and improved the performance in the behavioral tests. Conclusion: Our study points out that swimming during gestation in rats could prevent prematurity related brain damage in progeny with high translational potential and possibly interesting cost-benefits.